An updated review of experimental rodent models of pulmonary hypertension and left heart disease - Jasińska-Stroschein, Magdalena (Frontiers in Pharmacology, 2024)
Left heart disease (LHD) is the leading cause of pulmonary hypertension (PH). Its recent growth has not been matched by the design of therapeutic agents directly targeting the disease. Effective therapies approved for pulmonary arterial hypertension (PAH) have been shown to be inefficient in patients with PH-LHD. Hence, there is a need for an animal model that would closely mimic PH-LHD in preclinical experiments. The current study describes and compares a number of rodent models of left ventricle failure and their potential to induce PH. It also evaluates whether, and to what extent, common PH models could develop LV failure. Articles were identified in the Pubmed/Medline and Web of Science online electronic databases following the PRISMA Protocol between 1992-2022. Quality assessment was carried out using the SYRCLE risk-of-bias tool for animal studies. Publication bias across studies using Egger's regression test statistic, was performed together with sensitivity analysis. A wide spectrum of protocols -135 studies and 207 interventions, was examined, including systemic hypertensive models, pressure-overload-induced HF, model of ischemic heart failure, and metabolic approaches based on high fat diet or metabolic syndrome. The most pronounced alterations in PH-related parameters were demonstrated for the common PH models, but were also seen in animals with LV failure induced by ischemic conditions, pressure overload or metabolic conditions. Models based on aortic banding, transverse aortic constriction (TAC), or with myocardial infarction (MI) caused by coronary artery ligation, demonstrated more pronounced worsening in PH due to LV failure; however, they also demonstrated poor survival, especially the ischemic-HF model. Common PH models, excluding prolonged exposure to monocrotaline, do not promote LV hypertrophy. Prolonged exposure to a high-fat diet, or a two-hit model of an obese ZSF1 rat combined with SU5416-induced pulmonary endothelial impairment (a VEGF receptor antagonist) worsened PH and impaired diastolic dysfunction. Due to the limited number of protocols, further trials are needed to confirm the utility of such approaches for modeling PH in subjects with metabolic syndrome. This would provide a clearer insight into the complexity of LHD, PH and metabolic disorders in PH-LHD, and thus accelerate the development of new therapies in clinical trials.